From Belgrade to Madrid Conferences - Banionis, Juozas (Genocidas ir rezistencija, 2012)
Between the Belgrade and Madrid conferences, the main political organisations of the movement for the liberation of Lithuania acting in the West – the Supreme Committee for the Liberation of Lithuania (VLIK), Lithuanian American Council (ALT) and World Lithuanian Community (PLB) – acting both separately and jointly to seek a new quality of liberation activity, kept the case of Lithuanian liberation relevant in the West. The Supreme Committee for the Liberation of Lithuania, in the wake of a positive US Congress resolution concerning the Baltic States, changed its leadership and carried on fulfilling its promise to speak on behalf of the Lithuanian nation about its inalienable and unconditional right to restore sovereignty. Thus, with the Madrid conference approaching, the Supreme Committee for the Liberation of Lithuania deemed it important to use the final Helsinki Act to show the rest of the world that the rights of national self-determination of the Baltic nations were being trampled on, and that human rights were being infringed; they also wished to raise specific requirements with the Soviets: withdrawal of the oppressive administrative apparatus of the Soviet Union from Lithuania, the freeing of political prisoners and exiles, and respect for human rights and freedoms. The main target of the programme for the liberation of Lithuania by the American Lithuanian Council became the implementation of the principles of the final Helsinki Act. With the Madrid conference approaching, the American Lithuanian Council, having conceived those principles as “a new international legislative foundation” was determined to seek full rather than partial restoration of the freedom of Lithuania. Recognising its auxiliary role in the liberation process of Lithuania, the World Lithuanian Community foresaw that the deciding events would take place in Lithuania itself. As confirmation of this, the programme considering the issues of the order of the state of a liberated Lithuania, its borders and relations with its neighbours, was created. With the concept of liberation activities shifting, they focused on political actions, spreading information, and writing studies on events in Lithuania. Due to persistent disagreements between the Lithuanian American Council and the US Lithuanian Community, the Supreme Committee for the Liberation of Lithuania and the World Lithuanian Community, no general liberating conference to include all relevant parties was organised in the period between the Belgrade and Madrid conferences. But the free Lithuanian community, with assistance from the Lithuanian diplomatic service, agreed on a joint Lithuanian delegation to the conference held in the Spanish capital, Madrid. The unions of emigrant political organisations from the Baltic countries, reinvigorated by US Congress resolution No 200 adopted in 1979, which reiterated that the case for the liberation of their countries remained relevant, adopted a united position and deemed it necessary to continue political lobbyism and to act in a unified manner in both the West and during the conference of the Organisation for Security and Cooperation in Europe in Madrid.